Ultrasound-assisted external fixation: a technique for austere environments. Issue 6 (19th November 2015) - Talbot, Max; Harvey, E J; Reindl, R; Martineau, P; Schneider, P
Abstract : Introduction: Ultrasound-assisted external fixation of long bones has the potential to enhance extremity damage control surgery in locations without fluoroscopy, such as forward surgical elements, the intensive care unit, and spacecraft. This pre-clinical study specifically sought to evaluate orthopaedic surgeons' ability to sonographically define fracture patterns and the associated zone of injury in order to improve surgical decision-making and safely insert Schanz pin percutaneously. Methods: We encased small composite femurs in a cylindrical echogenic gelatin matrix to simulate a human thigh. Three orthopaedic trauma surgeons with no prior ultrasound experience were taught to use sonography to diagnose fractures and assist external fixation. The surgeons were then presented with five specimens in a randomized sequence: three diaphyseal fractures (32-A2, 32-C2 and 32-C3); a distal femur fracture (33-A1.2); and an intact femur, all encased in an opaque black gelatin matrix to blind the participants to the underlying pathology. If they diagnosed a diaphyseal fracture, the surgeons were instructed to insert two Schanz pins proximal and two distal to the fracture, no closer than 40 mm from the fracture edges. Results: Fracture diagnosis and surgical decision-making were correct in all cases. All intact femurs were recognized as such. The need for a knee-spanning external fixator was recognized for all distal femur fractures. The three surgeons performed appropriate ultrasound-assisted pin placement in every case of diaphyseal fracture. The pins adjacent to the fracture site were on average 58 mm (SD ±11 mm) from the edge of the fracture. No pins were inserted in the fracture or in the knee joint. Conclusions: The current study results suggest that with minimal training, orthopaedic surgeons can use portable ultrasound to diagnose femur fractures, decide the appropriate external fixator configuration, and safely insert Schanz pins outside the zone of injury.